Tela’ah Kritis Sistem Arisan Daging di Desa Tungkal Kecamatan Pino Raya dalam Perspektif Maslahah - Raga Pratama Satria Gusti; Miti Yarmunida; Miko Polindi (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the implementation mechanism of the meat arisan, identify the form of contract (akad) used, and examine the practice from the perspective of maslahah. This research employs a qualitative method with a field research approach. The data analysis technique used the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that the implementation mechanism of the meat arisan is carried out through the formation of a community group that collectively gathers regular contributions based on mutual deliberation to purchase livestock, which are then slaughtered and distributed equally among all members according to mutual agreement. The contract used in this practice is based on the principles of ta‘awun (mutual assistance), togetherness, and collective agreement conducted verbally through deliberation without formal written contracts. This practice reflects cooperation, mutual trust, willingness, and social responsibility without containing elements of riba. From the perspective of maslahah, the meat arisan provides significant economic, social, and religious benefits. Economically, it helps low-income communities obtain meat through a gradual payment system. Socially, it strengthens solidarity and the culture of mutual cooperation, while religiously it reflects the Islamic values of ukhuwah (brotherhood) and trustworthiness (amanah). Although there are still several challenges, such as administrative weaknesses and the absence of clear written regulations, the benefits gained are considered greater than the disadvantages, making this practice consistent with the perspective of maslahah.